2017
DOI: 10.1002/jhet.2846
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis Pairing Between Xanthene and Tetrazole in Pentacyclic System Using Tetrachlorosilane with Aurora Kinase Inhibitor Validation

Abstract: A competent new one-pot synthesis for tetrahydrobenzo [f]chromeno [3,2-c]tetrazolo[1,5-a]azepines through the catalytic synthesis of related xanthenes. β-naphthol, dimedone, aromatic aldehydes were stirred under solvent free condition in the presence of tetrachlorosilane (TCS), then azidochlorosilane (which prepared in situ from sodium azide and TCS in acetonitrile as solvent) was added and the reaction was stirred at 50-60 oC. A molecular docking of the synthesized compounds was carried out in order to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…ALP enzyme structure as a phosphate has been determined by X-ray technique [38]. The inhibition of ALP presents a unique challenge since the active site pocket is characteristically shallow and, in continuation of our work [39][40][41] to discover new drug enzyme interactions, we present this calculated part.…”
Section: Immunity Dockingmentioning
confidence: 96%
“…ALP enzyme structure as a phosphate has been determined by X-ray technique [38]. The inhibition of ALP presents a unique challenge since the active site pocket is characteristically shallow and, in continuation of our work [39][40][41] to discover new drug enzyme interactions, we present this calculated part.…”
Section: Immunity Dockingmentioning
confidence: 96%
“…Heterogeneous catalytic reactions for design and synthesis of heterocyclic compounds play an important role in our group, and so, this work was presented. The reaction started by optimization step to measure the efficiency of the prepared catalyst in organic synthesis especially in the preparation of polynuclear organic moieties and after the data obtained from this step we found that the best reaction condition as follows: The reaction is started by mixing two moles of 4‐hydroxycoumarin and one mole of benzaldehyde in the presence of V 2 O 5 /perovskite (NPs) at 60–70 °C under dry condition Scheme and on the way to prove the effectiveness of the synthesized catalyst we make comparable series of the same reaction and change the type of catalyst as perovskite, V 2 O 5 , and V 2 O 5 /perovskite respectively in the reaction between 4‐hydroxycoumarin and benzaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon of applying catalysis in the organic reaction is endlessly fascinating and perennially new. Our research group all time looking for discovering new catalysts and make their characterization then using them in organic synthesis development [20][21][22][23][24][25][26][27][28]. Herein we presented a new category of catalyst used to synthesis the significant class of organic compounds (BIM).…”
Section: Organic Reactionmentioning
confidence: 99%